Chronicle – Spring School on Acoustooptics and its Applications, XIIth Winter School on Molecular and Quantum Acoustics and Sonochemistry and XIth Winter School on Vibroacoustic Hazard Control in Industry, Seminar on Ultrasonic Nondestructive Testing - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1984)
Three years after the 1st Spring School on Acoustooptics and its Applications (Archives of Acoustics, 16, 3 (1981)), which had been held at Wieżyca near Gdańsk, another meeting in this field took place, organized by the Institute of Experimental Physics, Gdańsk University, in cooperation with the Section of Quantum and Molecular Acoustics and Sonochemistry of the Polish Acoustical Society and with support by the Institute of Fundamental Technological Research, Polish Academy of Sciences. On 1-6 March, 1984, at Ustroń-Jaszowiec, XIIth Winter School on Molecular and Quantum Acoustics and Sonochemistry and XIIth Winter School on Vibroacoustic Hazard Control in Industry were held at Ustrorń-Jaszowiec, both organized by High-Silesian Division of the Polish Acoustical Society in cooperation with the Institute of Physics of Silesian Technical University. The Seminar on Ultrasonic Nondestructive Testing was held at New Delhi on 5-6, December, 1983. The Seminar was organized by the Ultrasonic Society of India in collaboration with the National Physical Laboratory, New Delhi. It was inaugurated by Prof. Rais AHMED, Vice-Chairman, University Grants Commission, New Delhi.